Polarization‐Induced Buildup and Switching Mechanisms for Soliton Molecules Composed of Noise‐Like‐Pulse Transition States - Si, Zhi‐Zeng; Ju, Zhen‐Tao; Ren, Long‐Fei; Wang, Xue‐Peng; Malomed, Boris A.; Dai, Chao‐Qing (Laser & photonics reviews, 2025)
Buildup and switching mechanisms of solitons in complex nonlinear systems are fundamentally important dynamical regimes. Using a novel strongly nonlinear optical system, including saturable absorber metal‐organic framework (MOF)‐253@Au and a polarization controller (PC), the work reveals a new buildup scenario for “soliton molecules (SMs)”, which includes a long‐duration stage dominated by the emergence of transient noise‐like pulses (NLPs) modes to withstand strong disturbances arising from “turbulence” and extreme nonlinearity in the optical cavity. The switching between SMs and NLPs is controlled by the cavity polarization state. The switching involves the spectral collapse, following spectral oscillations with a variable period, and self‐organization of NLPs, following energy overshoot. This switching mechanism applies to various patterns with single, paired, and clustered pulses. In the multi‐pulses stage, XPM (cross‐phase‐modulation)‐induced interactions between solitons facilitate a specific mode of energy exchange between them, proportional to interaction duration, ensuring pulse stability during and after state transitions. Systematic simulations reveal the effects of the PC's rotation angle and intra‐cavity nonlinearity on the periodic phase transitions between the different soliton states and accurately reproduce the experimentally observed buildup and switching mechanisms. These findings can enhance the fundamental study and points to potential uses in designing information encoding systems. Using a novel strongly nonlinear optical system, including saturable absorber MOF‐253@Au and a polarization controller, the work reveals a new buildup and switching scenario for soliton molecules (SMs), which includes a long‐duration stage dominated by the emergence of transient NLPs modes to withstand strong disturbances arising from “turbulence” and extreme nonlinearity in the optical cavity.